Upgrade Path and Strategy of Logistics Industry Cluster Based on the Internet of Things - Jie Du (Hindawi Limited, 2021)
As the economy grows rapidly and IoT technology advances rapidly, the logistics industry as a service industry is growing rapidly around the world. The logistics industry, meanwhile, is the one that can best play the role of IoT. The rapid development of the logistics industry has brought great competition challenges to the logistics industry. To solve the competitive problems of the logistics industry cluster, this article introduces the research on the upgrade path and strategy of the logistics industry cluster based on the Internet of Things and uses the analytic hierarchy process, investigation method, and expert evaluation method to build the IoT technology information model and logistics cost. According to the established optimization model, the following are proposed: analyzing the problems existing in the logistics industry cluster, giving an upgrade path from the four aspects of manufacturing, technology, structure, and service, and giving specific strategic suggestions from the aspects of talents and enterprises. The accuracy rate of current analysis is as high as 90%, and the implementation rate of upgrade paths and strategy recommendations is as high as 95%.